Facile synthesis of silica aerogel composites via ambient-pressure drying without surface modification or solvent exchange. (March 2020) - Du, Dongxuan; Jiang, Yonggang; Feng, Junzong; Li, Liangjun; Feng, Jian
Abstract: Silica aerogels exhibit excellent properties, but their complex preparation procedure limits their broader applicability. Therefore, in the present study, mullite-fiber-reinforced silica aerogel composites (SACs) with low thermal conductivity were synthesized through ambient-pressure drying without surface modification or solvent exchange. The effect of the fiber volume content on the physical and mechanical properties and thermal conductivities of the composites was investigated. The results showed that the SACs with a fiber volume content of 5.7% exhibited the lowest thermal conductivity (0.101 and 0.0403 W m −1 K −1 at 1100 °C and room temperature, respectively), highest contact angle (158.2°) and compressive strength (0.1082 MPa at 10% strain), and lowest density (0.249 g cm −3 ) among the investigated SACs. Given the facile synthesis procedure and optimized performance of the SACs with a fiber volume content of 5.7%, this material is regarded as an effective and economical thermal insulation material. Highlights: Silica aerogel composites were synthesized via ambient drying. The surface of the silica aerogel composites is superhydrophobic (contact angle of 158.2°). Low thermal conductivity (0.101 W m −1 K −1 at 1100 °C) and good compressive property.